Penggunaan Media Gambar Dalam Keterampilan Berbicara Siswa Pada Pembelajaran Bahasa Indonesia Kelas III Di SDN Tenggilis Mejoyo I Surabaya - Hardiyanti Rukmana (LPPM Universitas PGRI Adi Buana, 2022)
The application of serial picture media is a learning that requires students to be active in learning, so that they can solve various practical problems and apply what they learn easily because students see or observe from their own experiences related to the topic being studied. One that was developed in grade 3 and is suitable for applying serial picture media to improve students' speaking skills in Indonesian language learning. The formulation of the problem in this study is